A novel biomimetic whisker technology based on fiber Bragg grating and its application. (21st August 2017) - Zhao, Chenlu; Jiang, Qi; Li, Yibin
Abstract: The paper describes a novel, biomimetic whisker-based sensing technology following the basic design of the facial whiskers of animals such as rats and mice. The sensor consists of a 3 × 2 whisker array on each side of a robot. In experiments with the artificial whiskers, the motor drives rotating whiskers, and the center wavelength of a fiber Bragg grating pasted on the whisker will shift when the whisker touches an obstacle. The distance will be obtained by processing the wavelength shift data with algorithms. Then the shape recognition can be realized by postprocessing the distance data. The experimental results prove that the whisker array is capable of accurately gathering the distance and shape information of an object.